A novel combined abdominal and vaginal approach for pelvic organ prolapse in young patients - Bhuyar, Sonal; Katkar, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
In India, the incidence of genital prolapse is 1.5 –2 % in nulliparous women and 5–8 % in young multiparous women which is the highest in the world. Though pelvic organ prolapse (POP) is not a life-threatening condition, its impact on life-style and self- esteem of a woman is paramount. There is a gamut of conservative surgical treatment options for POP for patients where the uterus needs to be preserved. Surgical repair in young women is more challenging as anatomical correction and preservation of fertility and sexual functions have to be addressed with a durable solution. In our case series, all three patients had third degree uterocervical descent with elongated and hypertrophied cervices. Hence neither abdominal nor vaginal repair alone was expected to be sufficient for restoring patient’s anatomy and sexual functions. Therefore, we came up with a novel combined abdominal and vaginal approach by carrying out cervical amputation vaginally and Virkud’s composite sling abdominally. The position and healing of the neo cervix was found to be excellent in all three cases during their post operative follow up. Through this case series, we highlight that the best surgical option for the treatment of POP should be tailored according to the patient’s need and expertise of the surgeon, as there are no clear guidelines for the choice of surgery for POP.